2000
DOI: 10.1016/s0741-5214(00)70079-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Dacron-activated monocytic cell oxidation of low density lipoprotein

Abstract: These results suggest that Dacron graft material activates monocytes to oxidize LDL by a mechanism that involves superoxide and requires iron and copper ions. Our work suggests a mechanism by which lipids that have been deposited within implanted vascular grafts may become oxidized. Oxidized lipids may contribute to the cellular dysfunction that results in anastomotic intimal hyperplasia and graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Dacron graft material used to activate U937 cells was prepared as previously described. 10 Briefly, Cooley Double Velour Knitted Dacron Graft (Meadox Medicals, Inc, Oakland, NJ) was cut into pieces measuring 1.25 ϫ 1.25 cm and weighing 80 Ϯ 5 mg; sequentially washed in 10 mmol/L EDTA, buffer, ethanol, and deionized water; and then plasma-sterilized. LDL oxidized by Dacron-activated U937 cells (oxLDL Dac ) was prepared by combining a Dacron graft piece, LDL (1000 g), and U937 cells (500,000) in 1 mL RPMI (that contains no added transition metal ions) and incubating for 24 hours, then centrifuging to remove graft fibers and cellular debris.…”
Section: Methodsmentioning
confidence: 99%
“…Dacron graft material used to activate U937 cells was prepared as previously described. 10 Briefly, Cooley Double Velour Knitted Dacron Graft (Meadox Medicals, Inc, Oakland, NJ) was cut into pieces measuring 1.25 ϫ 1.25 cm and weighing 80 Ϯ 5 mg; sequentially washed in 10 mmol/L EDTA, buffer, ethanol, and deionized water; and then plasma-sterilized. LDL oxidized by Dacron-activated U937 cells (oxLDL Dac ) was prepared by combining a Dacron graft piece, LDL (1000 g), and U937 cells (500,000) in 1 mL RPMI (that contains no added transition metal ions) and incubating for 24 hours, then centrifuging to remove graft fibers and cellular debris.…”
Section: Methodsmentioning
confidence: 99%
“…4 Oxidatively modified lipids and lipoproteins may have a role in recurrent stenosis after angioplasty and vascular graft failure, because oxidized low-density lipoproteins (oxLDL) possess a number of properties that would adversely affect healing, including inhibition of endothelial cell migration. 5 We have shown that Dacron graft material activates monocytic cells to oxidize low-density lipoprotein (LDL), 6 and that cell-modified LDL inhibits endothelial cell migration. 7 The mechanism by which oxLDL inhibits endothelial cell migration is an area of active investigation.…”
mentioning
confidence: 99%
“…Lipid oxidation products, but not native lipids or lipoproteins, cause cellular dysfunction in vitro, including inhibition of EC migration,4 stimulation of SMC proliferation,5 and increased platelet-derived growth factor (PDGF) and collagen production by SMCs,6, 7 which could impair graft healing in vivo. Studies have confirmed that prosthetic graft material induces monocytes to oxidize low-density lipoprotein (LDL),8 and lipid oxidation products accumulate in vascular grafts in vivo 9. In a previous rabbit study, hypercholesterolemia impaired prosthetic graft healing and was associated with increased anastomotic IH and macrophage infiltration and decreased endothelialization of the graft 10.…”
Section: Introductionmentioning
confidence: 99%